O impacto do risco inflacionário sobre os juros no Brasil - Tavares, Guilherme Aleixo (2007)
This article analyzes the connection between the public debt market and the monetary policy in Brazil. Based on a Vector Auto-Regressive model, two proxies of inflationary risk were used to show that positive shocks on inflation risk increases not only the future interest rates of Swap Pré x DI, but also the inflation market expectations. After that, based on Blanchard e Missale (1994) dynamic inconsistency model and using the Johansen methodology, we obtained that an increase in the futures interest rates decreases the maturity of the public debt, in the long termo These results permit us to take two conclusions: the inflationary risk 1) makes more difficult for the govemment to issue nominal debt in the market, generating a shorter structure of debt and 2) increases the cost of monetary policy.